Advanced smart computing technologies in cybersecurity and forensics - Kaushik, Keshav; Kaushik, Keshav; Tayal, Shubham; Bhardwaj, Akashdeep; Kumar, Manoj (Boca Raton CRC Press, 2022)
"This book addresses the topics related to artificial intelligence, internet of things, blockchain technology, and machine learning and brings together researchers, developers, practitioners, and users interested in cybersecurity and forensics"--
Detection of cross site scripting and phishing website vulnerabilities using machine learning / Sunil Sikka, Charu Jain, Aarti Chugh -- A review : security and privacy defensive techniques for cyber security using deep neural networks (DNNs) / Prachi Chauhan, Hardwari Lal Mandoria, Alok Negi -- DNA-based cryptosystem for connected objects and IoT security / Belhorma Brahim, Bouhedda Mounir, Bengherbia Billel, Benzineb Omar -- A role of digital evidence : mobile forensics data / G Maria Jones, S Godfrey Winster, L Ancy Geoferla -- Analysis of kernel vulnerabilities using machine learning / Supriya Raheja, Rakesh Garg, Bhavya Gururani -- Cyber threat exploitation and growth during Covid-19 times / Romil Rawat, Anand Singh Rajawat, Vinod Mahor, Bhagwati Garg -- An overview of the cybersecurity in smart cities in the modern digital age / Reinaldo Padilha, Ana Carolina Borges Monteiro -- The fundamentals and potential for cyber security of machine learning in the modern world / Reinaldo Padilha, Ana Carolina Borges Monteiro -- Qualitative and quantitative evaluation of encryption algorithms / Supriya Raheja, Rakesh Garg, Durgesh Pandey -- Analysis and investigation of advanced malware forensics / Apirajitha P. S., Punitha S, Thompson Stephan -- Network intrusion detection system using naïve Bayes classification technique for anomaly detection / Sam Goundar, Manveer Singh, Rahul Chand, Akashdeep Bhardwaj -- Data security analysis in mobile cloud computing for cyber security / Sam Goundar, Akashdeep Bhardwaj -- A critical review of legal and technical challenges during preliminary investigations of suspects of cyber crimes / Joshua Nehinbe -- Fault analysis techniques in lightweight ciphers for IoT devices / Priyanka Joshi, Bodhisatwa Mazumdar.
Includes bibliographical references and index.
Keywords: Computer security; Computer crimes